Curriculum Integration and Adaptation: Individualizing Pedagogy for Linguistically and Culturally Diverse Students - Tynisha Meidl; Christopher Meidl (Arizona State University, 2011)
In the United States, populations identified as linguistically and culturally diverse (LCD) are increasing at the fastest rate in public schools (Samway & McKeon, 2007). LCD students have not performed as well as their monolingual and/or affluent peers on state mandated assessments. No Child Left Behind Act (2001) stressed this disparity as âthe achievement gap,â resulting in highly structured curricular demands from districts forcing teachers to grapple between those demands and meeting the academic and cultural needs of LCD students. Using case-study methodology, this research explored how teachersâ beliefs about teaching and learning influence curriculum decision-making for LCD students. Through the triangulation of interviews, observations, and document analysis, three teachers and their students in a low-income, urban, k-4 school in a predominantly Spanish-speaking community was investigated. Participants integrated and adapted curriculum based on personal beliefs about teaching and learning, the needs of their LCD students, and the mandated curriculum.